Baricitinib for atopic dermatitis patients who responded inadequately to dupilumab treatment: First daily practice results - Linde deWijs; Corine Schreurs; Anne Schlösser; Tamar Nijsten; Dirk Jan Hijnen (Wiley, 2022)
Abstract Background Baricitinib is the first JAK inhibitor registered for the treatment of moderate‐to‐severe atopic dermatitis (AD). Efficacy and safety were shown in clinical trials, but daily practice data is sparse. Objectives To evaluate the effectiveness and safety of baricitinib treatment in daily practice in AD patients who have inadequately responded to dupilumab. Methods In this prospective observational cohort study, AD patients who failed dupilumab treatment and started baricitinib treatment in context of standard care at the Erasmus MC (the Netherlands) were included. We analysed physician‐reported scores and patient‐reported outcome measure scores (PROMs). Results Twenty‐five patients were included. Baricitinib treatment resulted in significant improvement of Eczema Area and Severity Index (EASI) scores and PROMs. Seven patients showed a good and sustained response (EASI50), eight patients showed no response (<EASI50), and five patients showed an initial response but worsening of EASI scores in time. Overall, baricitinib was well tolerated. Four patients discontinued baricitinib treatment due to ineffectiveness or side effects. Conclusions Baricitinib can be an effective treatment for a subset of AD patients who failed dupilumab treatment in daily practice. We found three different treatment response groups including responders, temporarily responders, and non‐responders.